Internationalization of Russian firms as institutional arbitrage: The case of Finland. - Victoria Golikova; Paivi Karhunen; Riitta Kosonen (European Regional Science Association (ERSA), 2013)
We analyze the internationalization of Russian firms based on a qualitative case study implemented in Finland. We empirically elaborate the concept of institutional arbitrage (Gaur and Lu, 2007; Boisot and Meyer, 2008), which refers to the situation where a firm is provided opportunities to exploit differences between two institutional environments. The sample consists of 12 Russian-owned firms located in Finland. The profile of the firms varied from subsidiaries of large MNCs to small firms established by entrepreneurs immigrating to Finland. Our empirical data provides support for the argument that the internationalization of Russian firms in many cases is as much escape from Russia as entry to the foreign market in search for a more favorable institutional environment. Furthermore, in some cases the ultimate goal may be to enter a particular foreign market, but prior achieving this goal the firm needs to escape from Russia and gather speed in an intermediate location in order to learn how to operate in an institutional environment different from Russia. The selection of this location is therefore not motivated by market potential or other traditional pull factors for internationalization. In our case the philosophy of such firms seems to be that the farther the test environment is from Russia in terms of institutional distance, the better it equips the firm to operate on other foreign markets as well. We conclude that the fact that the Russian institutional environment pushes firms and private investors to escape abroad provides also possibilities for institutional arbitrage. In our case this is demonstrated by possibilities to establish in Finland businesses, which are targeted to Russian customers seeking for safe haven for their capital in Finnish real estate, or who need support services for their international trade. Our analysis also points to the negative implications of institutional distance, and the root causes of institutional escape. The large magnitude of capital outflow from Russia, part of which has criminal origin, has made some foreign financial institutions suspicious to any Russian capital. From the perspective of policy-making, our interviews at the Russian-owned businesses in Finland discovered a strong commitment to operate according to the rules of the Finnish society and economy. Therefore, the potential prejudices towards Russian investors are in many cases without real basis. Finally, when drafting inward FDI promotion measures targeted to Russian investors, one should take into account the strong influence of personal motives for establishing business abroad that is characteristic for Russian entrepreneurs. It is not necessary the market potential and large profits that motivate internationalization, but rather the wish to establish one?s business and personal life in an environment less stressful and unstable than the Russian one.
Keywords: 330; Internationalization; institutional distance; institional arbitrage